2012
DOI: 10.3238/arztebl.2012.0695
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of the WHO Surgical Safety Checklist on Complication Rate and Communication

Abstract: These results support the WHO's recommendation to use the Surgical Safety Checklist in all operative procedures. The checklist should be understood not merely as a list of items to be checked off, but as an instrument for the improvement of communication, teamwork, and safety culture in the operating room, and it should be implemented accordingly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
120
0
26

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 110 publications
(146 citation statements)
references
References 39 publications
(20 reference statements)
0
120
0
26
Order By: Relevance
“…A landmark study published in 2009 illustrated that the implementation of the WHO SSC in varied socioeconomic settings worldwide was associated with marked improvements in surgical outcomes, including significant reductions in morbidity and mortality. 6 Numerous studies published since then have shown similar results, [7][8][9][10] and consequently the SSC has seen rapid and widespread adoption. 11 Many of these studies have shown compliance to be the most important factor for improved mortality and morbidity.…”
mentioning
confidence: 69%
“…A landmark study published in 2009 illustrated that the implementation of the WHO SSC in varied socioeconomic settings worldwide was associated with marked improvements in surgical outcomes, including significant reductions in morbidity and mortality. 6 Numerous studies published since then have shown similar results, [7][8][9][10] and consequently the SSC has seen rapid and widespread adoption. 11 Many of these studies have shown compliance to be the most important factor for improved mortality and morbidity.…”
mentioning
confidence: 69%
“…Fudickar A, et al 19 The beneficial effect of WHO safe surgery checklist showed a significant improvement in reducing the mortality and morbidity complication rate. He benefited in changing culture bringing positive effect and discussion of critical incidents, providing a reduction in the frequency of events.…”
Section: Resultsmentioning
confidence: 99%
“…One of the requirements to provide quality care and safe is to have an open communication culture, allowing teams an equal relationship where hierarchical rivalries become irrelevant. 19,20, In this sense, evidence communication as relevant factors to patient safety culture in health institutions is critical to the development of the work. The use of surgical safety checklist provides an opportunity for effective communication, allowing members of the surgical team to share expectations and clear and correct information reducing threats and complications.…”
Section: Vivekanantham S Et Al 26mentioning
confidence: 99%
See 2 more Smart Citations